Tinjauan Teknik Backhand Overhead Lob Atlet Persatuan Bulutangkis PB Warda Kota Padang - ⁠Fajri Muharman; Arif Fadli Muchlis; Ahmad Chaeroni; Fahmil Haris; Ridho Bahtra (MAN Insan Cendekia Jambi, 2026)
This study aimed to describe the backhand overhead lob technique of athletes at the Warda Badminton Club, Padang, and to identify the skill component that most requires improvement. A quantitative survey design using tests and measurements was employed. All 20 athletes in the population were included through total sampling. The performance test assessed initial stance, movement execution, accuracy, and successful shuttlecock placement using a 1-4 scoring scale that was converted to 0-100. Data were analyzed using descriptive statistics and percentages. The results showed a mean score of 77.19, a standard deviation of 14.52, a minimum of 56.25, and a maximum of 100. The distribution was 20% very good, 30% good, 10% moderate, 25% poor, and 15% very poor. Accuracy was the lowest component at 73.75%. The findings indicate uneven technical mastery and support differentiated training emphasizing footwork, contact point, coordinated movement sequencing, wrist acceleration, and progressive, repeated target-placement practice.